The Debate on Globalization and International Revitalization of Labor. A Critical Review - Fleming, Daniel; Søborg, Henrik (Nordic Journal of Working Life Studies, 2014)
This article discusses some alternative or critical theoretical contributions regarding globalization and labor. The main question in this discussion is if there are changes in direction of a possible revitalization of labor movements and if international solidarity can increase due to globalization. This question also relates to discussions of changes in division of work, the concept of work, working class, commodification, decommodification, and new centers of global production—all related to different paradigms or new concepts. The reason or need for reconceptualizing comes from the great transformation of capitalism in forms of neoliberal globalization, in a different direction than predicted by Polanyi. That is, instead of increased public sector decommodification (not profit- or market-oriented production) and national regulation, embedding capitalist markets, as seen after 1945, the last three decades have witnessed a countertransformation and large-scale recommodification by privatizing, disembedding, and deregulating global markets. As a consequence, inequality in income and working life conditions has increased in most countries and been used to press trade unions. Western industrial unions have been declining as many industries and labor-intensive, low-paid jobs moved to developing countries. Most blue-collar jobs are now in Asia, especially China, with about one-third of its employment blue collars. Is the center of global capital-labor contradictions and dynamics moving to the South, with a possibility of a new revitalization of labor and international solidarity? We discuss different optimistic and pessimistic views on a possible international revitalization of labor.